Synergistic enhancing effect of xanthan gum, carboxymethyl cellulose and citric acid on the stability of betacyanins in fermented red dragon fruit (Hylocereus polyrhizus) drink during storage - Lim, Teck Wei; Lim, Renee Lay Hong; Pui, Liew Phing; Tan, Chin Ping; Ho, Chun Wai (Elsevier, 2023)
Nowadays, the demand for using healthy natural pigments (betacyanins) in the food industry is increasing. The present study aimed to overcome the circumstances that render the betacyanins instability in the red dragon fruit drink using mild approaches. These included optimised fermentation, incorporation of anionic polysaccharide mixture solution xanthan gum (XG, 0.30–0.40 %, w/v) and carboxymethyl cellulose (CMC, 0.50–0.90 %, w/v) and also addition of citric acid (CA, 0.05–0.20 %, w/v). The results of this study showed that the hydrocolloid mixture solution of XG and CMC significantly increased the samples' viscosity, pH and °Brix but reduced the aw, while betacyanins concentration had no significant change. The incorporation of CA at increasing concentration only reduced the samples’ pH significantly without affecting the viscosity, aw and °Brix. Among all fermented samples, Formulation 3E (0.40 % XG + 0.50 % CMC + 0.20 % CA) had achieved the desired commercial reference viscosity while also successfully minimised betacyanins degradation from 60.18 % to 14.72 %, had the best pH stability and no significant change in viscosity, aw and °Brix values after 4-week storage at 25 °C. The fermented red dragon fruit drink with betacyanins stabilised by Formulation 3E can be produced and served as an independent functional drink product and as a stable, functional ingredient (natural colourant) for the food industry.